2012
DOI: 10.1055/s-0032-1329213
|View full text |Cite
|
Sign up to set email alerts
|

Long-term anticonvulsant therapy leads to low bone mineral density — evidence for direct drug effects of phenytoin and carbamazepine on human osteoblast-like cells

Abstract: Anticonvulsant therapy causes changes in calcium and bone metab olism and may lead to decreased bone mass with the risk of osteo porotic fractures. The two widely used antiepileptic drugs pheny toin and carbamazepine are recognized to have direct effects on bone cells. The aim of our study was to measure the influence of long-term treatment with antiepileptic drugs on bone mineral den sity (BMD) and to look on direct effects of carbamazepine and phenytoin on human osteoblast-like cells.BMD was measured by dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 25 publications
1
44
1
6
Order By: Relevance
“…According to bone histomorphometry in this study, phenytoin treatment significantly increased bone resorption, resulting in increase of eroded surface (ES/BS), osteoclast number (N.Oc/BS), and osteoclast surface (Oc.S/BS) in the proximal tibia metaphysis. Our data show that the observed decrease in BMD of phenytoin-treated rats is associated with elevated bone resorption, consistent with previous findings (11,37). Topiramate is a relatively weak carbonic anhydrase inhibitor that may result in adverse effects on bone metabolism by compliance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to bone histomorphometry in this study, phenytoin treatment significantly increased bone resorption, resulting in increase of eroded surface (ES/BS), osteoclast number (N.Oc/BS), and osteoclast surface (Oc.S/BS) in the proximal tibia metaphysis. Our data show that the observed decrease in BMD of phenytoin-treated rats is associated with elevated bone resorption, consistent with previous findings (11,37). Topiramate is a relatively weak carbonic anhydrase inhibitor that may result in adverse effects on bone metabolism by compliance.…”
Section: Discussionsupporting
confidence: 92%
“…A prospective study showed that the decrease in bone mineral density (BMD) of patients treated with phenytoin was 1.8%/year (9). Phenytoin has been reported to cause bone loss due to suppressed bone formation (24, 25) or enhanced bone resorption (11,37). In Europe and the United States, all the AEDs developed after the 1990s are classified as "newer AEDs".…”
mentioning
confidence: 99%
“…В более ранних работах рассматривались и другие ме-ханизмы воздействия фермент-индуцирующих ПЭП на ко-стную ткань: ингибирование ФТ всасывания кальция в ки-шечнике [23,24]; повышение активности остеокластов под влиянием ФТ [25]; ингибирование пролиферации остеобла-стов КБЗ или ФТ [6]; дефицит витамина К [26], дефицит кальцитонина [27]; увеличение уровня гомоцистеина [28]. Имеются противоречивые данные исследований о влиянии фермент-индуцирующих ПЭП на биохимические показате-ли костного метаболизма и МПК.…”
Section: традиционные пэпunclassified
“…Данные изменения связывают с дли-тельным применением противоэпилептических препаратов (ПЭП), типом ПЭП, политерапией и другими факторами [5][6][7][8]. Кроме того, высокая частота приступов, низкая фи-зическая активность, снижение концентрации внимания, координаторные нарушения, вызванные, помимо прочего, и приемом ПЭП, приводят к повышенной травматизации пациентов с эпилепсией [9,10] и увеличению риска перело-мов, обусловленных ОП.…”
unclassified
“…Furthermore, valproate, a CYP450 inhibitor, has also been shown to have an adverse effect on bone health, probably via completely different mechanisms (Sheth et al, 1995;Sato et al, 2001;Guo et al, 2001;. Decreased intestinal absorption of calcium, resistance to parathyroid hormone, calcitonin deficiency, interference with vitamin K metabolism, and a direct drug-effect on bone cell functions have also been suggested as possible mechanisms (Feldkamp et al, 2000;Petty et al, 2007). Other indirect effects of the drugs, such as hormonal changes, increases in homocysteine, reduction in insulin growth factor 1, and the effect of valproate as a histone deacetylase inhibitor, thereby reducing collagen I and osteonectin, may also contribute (Fuller et al, 2010).…”
Section: Effects On Bone Metabolismmentioning
confidence: 99%